CONSTRUCTION OF EXPRESSION VECTOR OF IMMUNOTOXIN ANTI-HER2-MELmmHERMEL) lN E.COLI - Dịu, Nguyễn Thị Thanh; Huyền, Lã Thị (Vietnam Journal of Biotechnology, 2011)
Since the discovery that the receptor HER2 (erbB2/neu) was overexpressed in 20 - 30% of breast cancers, and its subsequent association with poor prognosis, there has been many therapeutic strategies designed to fight against this kind of breast cancer. Immunotoxin therapy is one of a growing number of treatments in which scientists engineer molecules to target cancer cells and leave healthy cells unharmed. This hybrid molecule which is created by coupling an antigen or an antibody with all or part of a toxin combines the specificity of the antibody or antigen with the toxicity of the toxin. In this study we engineered an immunotoxin constituted by ScFv antiHER2 antibody and melittin, a cytotoxin originated from honey bee Apis cerana. The aim was to produce an immunotoxin having properties in specific recognition and lysis of the breast cancer cells overexpressing HER2. By using the methods in molecular biology, fusion of scFv anti-HER2 and melittin, was obtained from the cloning strain E. coli TOP 10 in our previous study. The fiision gene, namely hermei, was excised into pET-21a(+) expression vector (purchased from Invitrogen) and subsequently expressed in E. coli Rosetta (purchased from Novagen). Recombinant vector containing hermei gene was successfully designed. The sequence of hermei gene was registered with the code AM402973 in the GeneBank. The recombinant protein hermei was successfully overexpressed in E. coli Rosetta at a condition of 28°C and 0.6 mM IPTG, harvesting at 3 h after induction. The expressed immunotoxin with the size of 291 amino acids and molecular weight of approximately 32 kDa was purified by using Ni-NTA column (under the protocol of Invitrogen). Optimization in expression condition should be continuously studied in order to increase the yield of the expressed protein that can be subsequently subject to biological activity investigations and clinical trials.